REFORMING ESP IN UZBEKISTAN - Keljanova, Gozzal (Журнал иностранных языков и лингвистики, 2021)
This article is an attempt to understand the nature of English for Specific Purposes (ESP), tracing its history and development as well as about the EnSPIReU project which introduced a powerful approach in learning English and implementing new curriculum, syllabi, teaching materials, assessment criteria and training courses in the field of ESP in Uzbekistan.